Obesity as a risk factor for heart failure: overview of systematic reviews (Research, Society and Development, 2022)
The overweight and population with obesity has an increased risk of mortality from HF. However, some studies point to the existence of an "obesity paradox" where there could be a protective effect on the relative risk of death by HF in these populations with high BMI. In this way, the present study aimed to investigate obesity as a risk factor for heart failure. For this, an overview of systematic reviews was performed by selecting articles from the following databases: "Pubmed", "Scopus" and "SciElo”. A total of 615 articles were found from this initial search, leaving 59 articles for full-text reading, of which 22 articles were included for data extraction using the predefined inclusion criteria. From these 22 studies 73% were meta-analysis and 64% of the studies are of high methodological quality according to AMSTAR-2. Overweight and obesity have demonstrated a close relationship with the onset and increase of mortality by HF, studies have even been found that point to a gene interference in this relationship. In studies reporting on the obesity paradox, the results pointed to a momentary protection from mortality risk.